2016
DOI: 10.1016/j.dsr.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between infaunal communities of the deep floor and edge of the Tonga Trench: Possible effects of differences in organic matter supply

Abstract: a b s t r a c tHadal trenches are characterised by environmental conditions not found in any other environment, thereby providing new opportunities to understand the processes that shape deep-sea benthic communities. Technological advances have led to an increase in the number of investigations in hadal trenches over the last two decades. However, more quantitative samples including the deepest parts of trenches is needed to better understand trends in benthic diversity, abundance, biomass and community struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 54 publications
(123 reference statements)
7
29
1
1
Order By: Relevance
“…Similar patterns have been observed for nematodes (Tietjen 1989;Gambi et al 2003;Leduc et al 2016) and harpacticoid copepods (Kitahashi et al 2013). These trends are often ascribed to shifts in food availability, but the evidence is equivocal and other factors such as the physical characteristics of the sediment, disturbance and larger-scale evolutionary factors may also be important (Kitahashi et al 2013;Gambi et al 2003;Leduc et al 2016). The small size of trench habitats relative to the surrounding abyssal plains, as well as their geographical isolation, may limit both the size of species pools and connectivity among trenches, and may account for the limited diversity observed particularly in the deepest parts of trenches (Jamieson 2015).…”
Section: Metazoan Meiofaunasupporting
confidence: 85%
See 4 more Smart Citations
“…Similar patterns have been observed for nematodes (Tietjen 1989;Gambi et al 2003;Leduc et al 2016) and harpacticoid copepods (Kitahashi et al 2013). These trends are often ascribed to shifts in food availability, but the evidence is equivocal and other factors such as the physical characteristics of the sediment, disturbance and larger-scale evolutionary factors may also be important (Kitahashi et al 2013;Gambi et al 2003;Leduc et al 2016). The small size of trench habitats relative to the surrounding abyssal plains, as well as their geographical isolation, may limit both the size of species pools and connectivity among trenches, and may account for the limited diversity observed particularly in the deepest parts of trenches (Jamieson 2015).…”
Section: Metazoan Meiofaunasupporting
confidence: 85%
“…A number of early and recent studies have shown a negative relationship between depth and the diversity of benthic organisms within trenches (Belyaev 1972;Fujii et al 2013). Similar patterns have been observed for nematodes (Tietjen 1989;Gambi et al 2003;Leduc et al 2016) and harpacticoid copepods (Kitahashi et al 2013). These trends are often ascribed to shifts in food availability, but the evidence is equivocal and other factors such as the physical characteristics of the sediment, disturbance and larger-scale evolutionary factors may also be important (Kitahashi et al 2013;Gambi et al 2003;Leduc et al 2016).…”
Section: Metazoan Meiofaunasupporting
confidence: 55%
See 3 more Smart Citations